Islamic legal view on women’s marriage prohibition without knitting skills: A case study in Sukarara Village, Lombok - Saofi, M. Sulhan (Ex Aequo Et Bono Journal Of Law, 2024)
Background: The custom of weaving the clothes is a custom of the ancestors of the people of Sukarara Village, which must be carried out at weddings. Having weaving skills is a requirement that must be met for women before carrying out a marriage contract. If a woman does not have weaving skills, she is prohibited from carrying out the marriage. This article will discuss the problem of the practice of prohibiting marriage for women before they can weave in Sukarara Village, Jonggat District, Central Lombok Regency, and what the perspective of Islamic law is regarding the prohibition of marriage for women before they can weave in Sukarara Village, Jonggat District, Central Lombok Regency. Methods: Researchers used field research with a qualitative descriptive approach. Data collection techniques include observation, interviews, and documentation. Two data sources were used, namely primary data and secondary data. Findings: This research finds that the practice of prohibiting marriage for women who cannot yet knit traditional Lombok cloth has begun to erode. Conclusion: According to Islamic law, the prohibition of marriage for women before they can sesek is a marriage prohibition that can be justified because: First, it brings benefits to each individual and many people. Second, it is included in the authentic urf as long as it does not conflict with Islamic teachings. Novelty/Originality of this Study: The intersection between local customs and Islamic law, specifically focusing on the unique tradition in Sukarara Village that prohibits women from marrying until they can weave traditional Lombok cloth, offers a rare insight into the coexistence and mutual influence of cultural practices and religious principles on marriage laws in a specific Indonesian community.